2012
DOI: 10.1177/0037549712443404
|View full text |Cite
|
Sign up to set email alerts
|

Automated input data management: evaluation of a concept for reduced time consumption in discrete event simulation

Abstract: Input data management is a crucial and time-consuming part of a simulation project. Consequently, improvement of this process has substantial potential to increase the rapidity of simulation projects, thus enabling more detailed analyses in design and development of production systems. This paper presents the development of a concept and an associated software demonstrator called the Generic Data Management Tool (GDM-Tool), which automates several critical and time-consuming data input activities. More specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In contrast to [18] the major advantage of this tool is that it is OS (GNU Lesser General Public License (LGPL)), so easily accessible by anyone interested in developing the concept of automating simulation input data. The KE tool is also developed using Python, a language that is widely being used by scientist due to the ease of programming [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to [18] the major advantage of this tool is that it is OS (GNU Lesser General Public License (LGPL)), so easily accessible by anyone interested in developing the concept of automating simulation input data. The KE tool is also developed using Python, a language that is widely being used by scientist due to the ease of programming [27].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested the use of CMSD, designed by the Simulation Interoperability Standards Organization (SISO) [16] in order to support the identification and decision of the parameters required for the simulation application. A more generic input data methodology is proposed by Bengtsson et al [17], which uses the GDMTool [18] that implements CMSD.…”
Section: Input Data Management In Desmentioning
confidence: 99%
“…FACTS is a research project that finished in March 2008 [19], which resulted in two tools, one of them is the GDMTool [20]. The GDM-Tool aim is aimed to allow the automatic integration of production data into the DES models stored in different IT-systems at companies [21].…”
Section: Cmsd Related Researchmentioning
confidence: 99%
“…Translating among these interfaces is time consuming. For example, (Skoogh 2009) showed that more than 30% of the total time to develop simulation models is spent on gathering, extracting, and processing data. To facilitate application interoperability, SPAF will provide a common method for describing and encoding SM process information.…”
Section: The Need For the Proposed Frameworkmentioning
confidence: 99%